(untitled) (European Journal of Marketing and Economics, 2024)
When resources are scarce at crisis times and when competition is intense with other creative supplies, USA symphony orchestras and opera houses memorize and perform their repertoires (or repertories), so that seasons are crucially bundled between tradition and innovation. Since the beginning of the latest financial and real crisis (2007), USA classical music has seen different levels of funding from the federal government and businesses have encouraged more nonconventional programming (Pompe, Tamburri, 2016; Turbide, Laurin, 2009; Ravanas, 2008; Rushton, 2008; Turrini, 2006; Smith, 2007). On one side, fundraisers have stressed bundles (contemporary music with tradition) to sponsors; on the other side, marketing officers have emphasized the repertoire memory to audiences who constantly love Traviata, Boheme and Don Giovanni with echo of famous regisseurs, scenographers, etc. This is quite the same worldwide (Cancellieri, Turini, 2016). Fundraising and marketing affect economic performances of classical music, also thanks to social media and networks. Consumers have access to information about ticketing, rehearsals, present and past performances, etc. Art organizations strive to manage communication via social media to create brand values. Social media support both fundraising and marketing, as they mediate to sponsors and audiences: values, advocacy, videos and photos of the repertoire and nonconventional programming, which continually increase trustworthy relationships and nurture memories.This paper investigates 200 USA symphony orchestras and opera houses according to repertoires, revenues, expenses and gains in 2008 and 2015. With cluster analysis, three profiles emerge with different strategies, performances and emphasis on memory or innovation.